Receptor tyrosine kinases Tyro3, Axl, and Mertk differentially contribute to antibody-induced arthritis - Liang Gao; Chao He; Aizhen Yang; Haibin Zhou; Qingxian Lu; Raymond B. Birge; Yi Wu (Cell Communication and Signaling, 2023)
Abstract Tyro3, Axl, and Mertk (abbreviated TAMs) comprise a family of homologous type 1 receptor tyrosine kinases (RTKs) that have been implicated as inhibitory receptors that dampen inflammation, but their roles in the pathogenesis of rheumatoid arthritis remains understudied. Here, to investigate TAMs in an inflammatory arthritis model, antibody-induced arthritis in single TAM-deficient mice (Tyro3- KO, Axl-KO, Mertk-KO) was induced by K/BxN serum injection. Subsequently, joint inflammation and cytokine levels, as well as the expression of Fcγ Rs and complement receptors were assessed in WT and TAM-deficient mice. Compared with littermate control mice, Axl−/− and Mertk−/− mice developed more severe antibody-induced arthritis, while in contrast, Tyro3−/− mice showed diminished joint inflammation. Concomitantly, the levels of cytokines in joints of Axl−/− and Mertk−/− mice were also significantly increased, while cytokines in the Tyro3−/− joint tissues were decreased. At the molecular and cellular level, TAMs showed distinct expression patterns, whereby monocytes expressed Axl and Mertk, but no Tyro3, while neutrophils expressed Axl and Tyro3 but little Mertk. Moreover, expression of Fcγ receptors and C5aR showed different patterns with TAMs expression, whereby FcγRIV was higher in monocytes of Axl−/− and Mertk−/− mice compared to wild-type mice, while Tyro3−/− neutrophils showed lower expression levels of FcγRI, FcγRIII and FcγRIV. Finally, expression of C5aR was increased in Mertk−/− monocytes, and was decreased in Tyro3−/− neutrophils. These data indicate that Axl, Mertk and Tyro3 have distinct functions in antibody-induced arthritis, due in part to the differential regulation of cytokines production, as well as expression of FcγRs and C5aR. Video Abstract